Efficient separation performance of suspended soil and strontium from aqueous solution using magnetic flocculant. Issue 6 (December 2021) - Lee, Hyun-Kyu; Kim, June-Hyun; Kim, Ilgook; Jeon, Hongrae
Abstract: This study aimed at magnetically separating suspended soil and Sr 2+ from a soil suspension using a magnetic flocculant (MNP/IF). MNP/IF was prepared using the electrostatic interaction between the magnetite particles and the inorganic flocculant (IF) based on CaCO3 and Na2 SO4 . By analyzing the physical properties of MNP/IF, it was confirmed that MNP/IF was successfully imparted with magnetism and had excellent adsorption capacity for Sr 2+ . The optimal MNP/IF dosage for the sedimentation of suspended soil was determined to be 0.3 g/g (mass ratio of flocculant to soil). Compared with raw IF, MNP/IF showed better flocculation performance to suspended soil for a shorter sedimentation time. The lower the pH, the more favorable the flocculation-sedimentation process of the suspended soil by MNP/IF, since Ca 2+ and Mg 2+, which are the most common strong flocculators, were further eluted from IF under acidic conditions. MNP/IF also showed excellent removal performance for Sr 2+, exhibiting maximum Sr 2+ adsorption capacities of 163.6 mg/g in the flocculation-sedimentation reaction of suspended soil. The Sr 2+ adsorption process was consistent with the Langmuir model and followed the pseudo-second-order kinetics. These results provide that MNP/IF can be used for the simultaneous removal of suspended soil particles and Sr 2+ from a radioactive soil suspension. Graphical Abstract: ga1 Highlights: MNP/IF was prepared using electrostatic attraction forces between MNPs and IF. MNP/IF formed stable flocs with suspended soil, easily separated by magnetic force. At low pH, flocculation-sedimentation of suspended soil by MNP/IF is more favorable. IF plays a major role in Sr 2+ adsorption by ion exchange of Ca 2+ with Sr 2+ .